Clara Barton : angel of the battlefield - Lassieur, Allison; Bascle, Brian (Mankato, Minn. : Capstone Press, 2006)
Presents the life of Clara Barton, focusing primarily on her work as a nurse during and after the Civil War and her efforts on behalf of the Red Cross.
The making of a heroine -- The Civil War -- One war ends, another begins -- The American Red Cross.
Includes bibliographical references (p. 31) and index.
Keywords: Barton, Clara, -- 1821-1912 -- Juvenile literature; Nurses -- United States -- Biography -- Juvenile literature